BIOACTIVE COMPOUNDS PRESENT IN AEGLE MARMELOS AND THEIR ROLE IN MEDICINAL PROPERTIES: A REVIEW - NIDHI SHARMA; WIDHI DUBEY (International Journal of Pharma and Bio Sciences, 2016)
Plants used by ethnic groups are proved to be a rich source of novel drugs that form the ingredients in traditional and modern systems of medicines. Pharmacological studies have acknowledged the value of ethnomedicinal plants as prospective source of bioactive principles. Aegle marmelos (L.) Corr. Serr. of family Rutaceae, commonly known as wood apple plant, is one of the important plants with medicinal and nutraceutical properties. It can tolerate a wide range of climatic conditions and used as a panacea for various ailments by tribal people throughout the world. This review has been done to find out the role of various bioactive compounds present in the plant parts of A. marmelos in medicinal properties.